New genera and new species of remarkably large-sized or uniquely-shaped mirine plant bugs from Taiwan (Heteroptera: Miridae: Mirinae) - Yasunaga, Tomohide; Yamada, Kazutaka; Tsai, Jing-Fu (Zootaxa, 2023)
New taxa are proposed and described for several large-sized or uniquely-shaped mirine plant bugs from Taiwan or the northeastern Oriental Region. Two new genera, Rhopalimiris n. gen. and Taiwanocapsus n. gen. are described to accommodate three new species, Rhopalimiris amplissimus n. sp., R. gagai n. sp. and Taiwanocapsus luteocordatus n. sp., which are diagnosed and described. In addition, new species of Eocalocoris Miyamoto & Yasunaga and Eurystylus Stål, namely Eo. gotohi n. sp. and Eu. yixuanae n. sp., are also described. An updated checklist of the Taiwanese Mirini is also provided.